Efficiency analysis of PAPR reduction schemes - Razavi, Sara; Sulaiman, Nasri; Mohammady, Somayeh; Mohd Sidek, Roslina; Varahram, Pooria
Orthogonal frequency division multiplexing (OFDM) is a robust transmission technique to combat the influence of wireless fading channels. However, OFDM suffers from high peak-to-average power ratio (PAPR) that significantly reduces the efficiency of the high power amplifier (HPA). This paper reviews the performance of few PAPR reduction techniques that are mostly based on Selected mapping (SLM), and Dummy sequence insertion (DSI) algorithms for orthogonal frequency division multiplexing (OFDM) systems.